Pathogenesis Interrelation of Insufficiency of Erythrocytes Antiradical Protection and Disturbance of Blood Rheological Properties in Bacterial Endotoxicosis - G.A. Afanas`eva; N.P. Chesnokova; V.V. Kutyrev (Проблемы особо опасных инфекций, 2009)
Among the leading pathogenesis factors of disorders of regional blood flow and microcirculation in plague intoxication induced by Y. pestis lipopolysaccharide (LPS) are decreases of blood viscosity at various shift rates, indices of erythrocyte deformation and aggregation that correlate with severity of clinical manifestation. Efferent part of LPS cytopathogenic effects of plague microbe is enhancement of free-radical oxidation and formation of anti-oxidative system deficiency.